2021
DOI: 10.3390/membranes11020080
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Cellulose Acetate Mixed-Matrix Membranes for Improved Oil–Water Separation: Comparison between Sodium and Organo-Montmorillonite as Particle Additives

Abstract: In this study, cellulose acetate (CA) mixed-matrix membranes were fabricated through the wet-phase inversion method. Two types of montmorillonite (MMT) nanoclay were embedded separately: sodium montmorillonite (Na-MMT) and organo-montmorillonite (O-MMT). Na-MMT was converted to O-MMT through ion exchange reaction using cationic surfactant (dialkyldimethyl ammonium chloride, DDAC). Attenuated total reflectance-Fourier transform infrared (ATR-FTIR) and X-ray photoelectron spectroscopy (XPS) compared the chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…This is followed by CA and PSF membranes with the surface water contact angles of 74.5 and 70.23°, respectively. The surface water contact angle of plain CA membrane from commercial polymers in this study is within the range reported earlier of 50-60° [38][39][40], which can be attributed to the variation surface structure and fabrication parameters and possibly due to the presence of impurities that can be further investigated as the follow-up study. These findings are encouraging and show that a CA membrane based from cigarette butt waste potentially possess a high clean water permeability and good anti-fouling property, at least when compared with the PVDF and PSF membranes samples used as a reference in this study.…”
Section: Surface Contact Anglesupporting
confidence: 86%
See 1 more Smart Citation
“…This is followed by CA and PSF membranes with the surface water contact angles of 74.5 and 70.23°, respectively. The surface water contact angle of plain CA membrane from commercial polymers in this study is within the range reported earlier of 50-60° [38][39][40], which can be attributed to the variation surface structure and fabrication parameters and possibly due to the presence of impurities that can be further investigated as the follow-up study. These findings are encouraging and show that a CA membrane based from cigarette butt waste potentially possess a high clean water permeability and good anti-fouling property, at least when compared with the PVDF and PSF membranes samples used as a reference in this study.…”
Section: Surface Contact Anglesupporting
confidence: 86%
“…Polymer purification was shown effective in improving the structure and performance of the resulting membranes [42]. The spectra shown in Figure 6 resemble the one obtained for the phase inverted membrane prepared from the commercial CA polymer [40,41]. The presence of impurities is hardly seen from the spectra, indicating that the spectra associated with them might be overlapping with the spectra associated with CA.…”
Section: Fourier Transform Infraredmentioning
confidence: 72%
“…In addition, PESPDA0.3 and PESAg-PDA0.3 had similar thickness. During the phase inversion process, the hydrophilic nanofillers enhanced the demixing rate, thus resulting in a thicker membrane [56]. Figure 5a reveals that gaps between peaks and valleys on the PES were uniform and smooth, indicating the low surface roughness of the investigated membranes.…”
Section: Characterization Of the Membranesmentioning
confidence: 99%
“…Prior to the nanofiltration test, membranes were washed using deionized water. Membranes were installed in a lab-scale crossflow filtration setup, which is similar to our previous work [56]. Before measuring the pure water flux, membranes were prepressurized at 4.5 bar for 1 h to ensure a steady-state condition.…”
Section: Evaluation Of Membrane Performancementioning
confidence: 99%
See 1 more Smart Citation